PENGARUH LAMA PENGOMPOSAN DAN KOMPOSISI MEDIA CAMPURAN AMPAS AREN DAN JERAMI PADI TERHADAP HASIL JAMUR MERANG (Volvariella volvaceae (Bulliard Ex Fries) Singer) - Rian Widiyanto; Hadi Rianto; Historiawati Historiawati (JURNAL VIGOR, 2018)
This research is to study the effect of composting time and media composition of sugar palm solid waste and  straw to an yield of straw mushroom (Volvariella volvaceae (Bulliard Ex Fries) Singer). The research held on May until June 2018. Location of this research is at Kedungsari village, Bandongan sub-district, Magelang regency. The altitude is 332 meters. Factorial experiments 4 x 3 in randomize complete block design that consist of 4 repetitions. First factor is composting time 3, 5, 7, and 9 days. Second factor is media compositions of mix sugar palm solid waste and rice straw (2% : 10%), (4% : 3%), (10% : 10%). The result of this research shows that lenght of composting declines total number of fruits bodies, total weight of fruits bodies, and biological  efficiency. Biological efficiency of  media composition about 10.22% - 19.16%. Media composition of sugar palm solid waste and rice straw do not  effect all observe parameters. Top rack position gets higher yield on total number of fruit bodies per plot, total weight of fruit bodies per plot, and biological efficiency.Composting time is three days on the composition media (10% : 10%) is more effective to the first harvest with the high yield of paddy straw mushroom.